The Military Journal Zarubezhnoe Voennoe Obozrenie Under Perestroika (1985-1991) - Sophie Momzikoff (Journal of Power Institutions in Post-Soviet Societies, 2014)
This article aims to present the evolutions of the military journal Zarubezhnoe voennoe obozrenie (ZVO)’s life during the perestroika years (1985-1991). The journal’s main mission was to picture the state of Western armed forces, using data collected in the Western press. Recent historical researches carried after the crushing of the Soviet State have shown that journalists or policy analysts in contact with foreign sources participated in the opening of Soviet media landscape and produced a new and less ideological discourse. The purpose is therefore to determine if the same applies to ZVO’s journalists. Considering the general context of glasnost and the journal’s close contacts to Western sources, was ZVO in the vanguard of the change process affecting military journalism in Soviet Union? Or did it remain a bastion of tradition?